Organizational factors for risk control: Comparison between face-to-face and remote training methods. Analysis of the performance of workers working in the construction of electrical networks. (Research, Society and Development, 2022)
Accidents at work are events that bring losses to the employee, employer and society, both economically and socially. Employee training is an important tool for reducing the number of deviations and, consequently, of occupational accidents and diseases, having a crescent in the remote method during the pandemic. Thus, this paper seeks to demonstrate whether the transition to the remote method of training has changed or altered the way workers act safely in the process of electrical network construction. It also establishes guidelines for the adequate use of digital tools in corporate training, and the professional profile of greater adherence to this type of training. The methodology was divided into four parts, as follows: Literature review; field study, where face-to-face and remote training was conducted; evaluation criteria for the workers who participated in the study; and statistical treatment and data analysis. The workers who did the remote theoretical training had an average of 8.6, while those who did the face-to-face training had an average of 8.0. In the practical training, those who were trained remotely had an average score of 9.0, while those trained in person had an average score of 8.0. The professionals trained through virtual platforms showed similar performance compared to those who received traditional training, when we consider the standard deviations of the statistical analysis. The results indicate that there was no loss in the perception of risk for employees trained virtually, however, the cost of in-person training is 26 times higher than that of remote training.